Inclusive Universities. Exploring the well-being of university students with special needs in Albania - Zenelaga, Brunilda; Goga, Aida; Králik, Roman (Journal of Education Culture and Society, 2024)
Aim. The purpose of this study is to explore the issue of the inclusion of university students with special needs (USSN) in universities and their social well-being, based on the case of the Faculty of Social Sciences at the University of Tirana in the Republic of Albania. Methods. The methodology used is based on the combination of secondary sources, with primary ones, provided through the interview of the academic and administrative staff, parents and students. Results. The study highlighted that in the Republic of Albania important positive steps have been taken in improving the legislation of Higher Education regarding the inclusion of UUUUSSN in universities. This has been successfully adapted to the Unaiversity Statute of the University of Tirana. Also, the study highlighted that even from the infrastructural aspect, some opportunities have been created for USSN in this faculty, but they are still insufficient. The lack of protocols and individual programmes for the treatment of USSN is a necessity. Regardless of these shortcomings and some people’s skepticism about the participation of USSN in university education, a friendly climate is created in this faculty, in function of the social well-being of USSN. Conclusions. As a conclusion, the adaptation of the philosophy of inclusion in concrete practices is met with numerous challenges. Regarding the creation of a friendly climate in function of the social welfare of USNS, the case of the Faculty of Social Sciences at the University of Tirana constitutes a positive model, which should be promoted.